Pemanfaatan Pemasaran Digital: Meningkatkan Potensi Ekspor Briket Arang Tempurung Kelapa dalam Bisnis Internasional - Phung, Cavin Kleinsteuber; Wikartika, Ira (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research is about the role of digital marketing in exporting Indonesian coconut shell charcoal briquettes to the global market. Coconut shell charcoal is a top commodity in Indonesia due to the quality of coconuts grown there. However, in order to export, businesses need to put in extra effort in global marketing and sales. This research uses a qualitative literature study method to identify the steps that businesses can take to utilize digital marketing. The results of this research reveal the ease of maximizing digital features to effectively and efficiently reach international markets.